Transições de fase do Modelo Primitivo Restrito para eletrólitos com interações de curto alcance - Velasque, Luciana Araújo (2010)
In this work, the phase behavior of the restricted primitive model (RPM) for symmetrical electrolytes in the presence of short-range potentials is examined. A simple model is presented, combining the Debye-H¨uckel-Bjerrum with dipolo-ion interaction and the van der Waals theory representing an effective short-range attraction between the ions. The phase diagram is examined as a function of the strength ε of this attraction and different scenarios are proposed. In the region of small ε, the phase behavior is driven by electrostatic interaction and a RPM phase coexistence is obtained. When ε is increased, the van der Waals critical point, that was metastable inside the RPM coexistence, increases its temperature and becomes stable. We show that for a certain region of ε both RPM and van der Waals critical points coexist in equilibrium. Increasing even more the strength of short-range attraction, the RPM critical point becomes metastable and the phase behavior is driven by van der Waals interaction. We discuss the physical implications of this behavior and compare our results with Monte Carlo simulation and field-theoretical approaches.